2011
DOI: 10.1186/1750-1326-6-52
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cathepsin D in the caudate nucleus of primates with experimental parkinsonism

Abstract: BackgroundIn Parkinson's disease there is progressive loss of dopamine containing neurons in the substantia nigra pars compacta. The neuronal damage is not limited to the substantia nigra but progresses to other regions of brain, leading to loss of motor control as well as cognitive abnormalities. The purpose of this study was to examine causes of progressive damage in the caudate nucleus, which plays a major role in motor coordination and cognition, in experimental Parkinson's disease.ResultsUsing chronic 1-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Interestingly, human cells were not proven to have any inhibitors of CTSD, excluding DNA fragments and its propeptide detached during activation . In vitro study showed that overexpression of CTSD led to a significant increase of the number of the lysosomes in human neuroblastoma cells, which resulted in extralysosomal CTSD and was accompanied by associated with caspase activation resulting in significant neuronal death . Our study was in agreement with Chen's study, who found that CTSD exhibited more than 1.5‐fold upregulation in male amniocytes rather than female amniocytes .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, human cells were not proven to have any inhibitors of CTSD, excluding DNA fragments and its propeptide detached during activation . In vitro study showed that overexpression of CTSD led to a significant increase of the number of the lysosomes in human neuroblastoma cells, which resulted in extralysosomal CTSD and was accompanied by associated with caspase activation resulting in significant neuronal death . Our study was in agreement with Chen's study, who found that CTSD exhibited more than 1.5‐fold upregulation in male amniocytes rather than female amniocytes .…”
Section: Discussionsupporting
confidence: 90%
“…In control cells, the punctate distribution of Cat D (green stain) and LAMP-2 (red stain) and their co-localization (r ϭ 0.825) upon the merge, resulting in yellow stained lyso- somes, is indicative of undamaged lysosomes/autolysosomes (Fig. 10A) as shown previously (69). Incubation with TAM enhanced the punctate fluorescence pattern of both Cat D and LAMP-2 and their co-localization (r ϭ 0.944) in the merge relative to the control (Fig.…”
Section: Dp44mt and Dfo Increase Lc3-ii Levels And Autophagosome Formmentioning
confidence: 68%
“…Results from a recent cell culture study showed that, similar to GCase, deficiency of cathepsin D leads to increased cell‐to‐cell transmission of α‐synuclein aggregates . Paradoxally, in vivo and in vitro studies have reported opposite effects, as the expression of cathepsin D was shown to be upregulated in the striatum of a monkey MPTP model of PD and in fibroblasts from PD patients with GBA mutations, respectively . Although cathepsin D was initially suggested to be the main protease involved in α‐synuclein degradation, a recent study argued this notion because cathepsin D generates amyloidogenic C‐terminal truncated species and therefore requires the assistance of other proteases .…”
Section: The Degradation Of α‐Synuclein By Different Proteolytic Systemsmentioning
confidence: 99%